(3LeY GdfgGjHI aj HOA GdNjQ hZGjgs - (3GHf CHj LeQI, YHO Gddg Hf SYO Hf SYjO, J (B695 (3g`s ((3MSjf UGdM Hf eMeO UGdM GdTjN Ydj GdjHQhOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; hGdJUdjI , GdMeO ddg Mb MeOg hGdUdGI hGdSdGe Ydi eMeO GdNjQI ef Ndbg hHYO adeG cGf GdMOjK hMaXg ef CbQH GdhSGFd Edi Gddg YR hLd HebJVi GdBKGQ aQCjJ Cf BNP ef CUM cJHg cJGHG CNJUQ efg CMGOjK HMSH GdMGLI EdjgG aSejJg HebJVi hVYg LeY GdfgGjI aj HOA GdNjQ hZGjg s
(3BNQgG (B:s
(3Yf CHj SYjO GdNOQj QVj Gddg Yfg bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B: " (3Ef Gddg JYGdi jbhd dCgd GdLfI(B: (3jG Cgd GdLfI, ajbhdhf(B: (3dHjc QHfG hSYOjc, hGdNjQ cdg aj jOjc, ajbhd(B: (3gd QVjJe? ajbhdhf(B: (3heG dfG dG fQVi jG QH, hbO CYWjJfG eG de JYW CMOkG ef Ndbc? ajbhd(B: (3CdG CYWjfce CaVd ef Pdc (B( (3cPG (B) (3ajbhdhf(B: (3jG QHfG, hCj TjA CaVd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 89s
(3eYLe GdeDdajf (B2 / 234s
(3cTa GdXfhf (B1 / 599s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdMOjK hGdeUWdMs